Fabrication of Ti substrate grain dependent C/TiO2 composites through carbothermal treatment of anodic TiO2. Issue 13 (15th March 2016) - Rüdiger, Celine; Favaro, Marco; Valero-Vidal, Carlos; Calvillo, Laura; Bozzolo, Nathalie; Jacomet, Suzanne; Hejny, Clivia; Gregoratti, Luca; Amati, Matteo; Agnoli, Stefano; Granozzi, Gaetano; Kunze-Liebhäuser, Julia
Abstract : The crystallinity of anodic TiO2 and its activity towards C2 H2 decomposition are affected by the texture of the Ti substrate. Abstract : Composite materials of titania and graphitic carbon, and their optimized synthesis are highly interesting for application in sustainable energy conversion and storage. We report on planar C/TiO2 composite films that are prepared on a polycrystalline titanium substrate by carbothermal treatment of compact anodic TiO2 with acetylene. This thin film material allows for the study of functional properties of C/TiO2 as a function of chemical composition and structure. The chemical and structural properties of the composite on top of individual Ti substrate grains are examined by scanning photoelectron microscopy and micro-Raman spectroscopy. Through comparison of these data with electron backscatter diffraction, it is found that the amount of generated carbon and the grade of anodic film crystallinity correlate with the crystallographic orientation of the Ti substrate grains. On top of Ti grains with ∼(0001) orientations the anodic TiO2 exhibits the highest grade of crystallinity, and the composite contains the highest fraction of graphitic carbon compared to Ti grains with other orientations. This indirect effect of the Ti substrate grain orientation yields new insights into the activity of TiO2 towards the decomposition of carbon precursors.